2010
DOI: 10.1021/jp9104536
|View full text |Cite
|
Sign up to set email alerts
|

A TDDFT Study of the Fluorescence Properties of Three Alkoxypyridylindolizine Derivatives

Abstract: The fluorescence properties of three pyridylindolizine derivatives (one tricarbomethoxy-7-pyridyl-pyrrolopyridine and two dicarboethoxy-3-bromobenzoyl-7-pyridyl-pyrrolopyridines) have been investigated by applying density functional theory (DFT) and the time-dependent DFT (TDDFT). Performances of two hybrid-type functionals (BH&HLYP and B3LYP) and one generalized gradient approximation (GGA) functional (PBE) as well as three basis sets (SV(P), DZP, and TZVP) have been assessed. The solvent environment has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…However, to obtain the best agreement between the theoretically predicted and experimentally derived values, use of different functionals and basis sets can be important. Several examples supporting this notion can be found in literature …”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, to obtain the best agreement between the theoretically predicted and experimentally derived values, use of different functionals and basis sets can be important. Several examples supporting this notion can be found in literature …”
Section: Introductionsupporting
confidence: 93%
“…Several examples supporting this notion can be found in literature. [16,17] In this context, the present investigation includes:…”
Section: Introductionmentioning
confidence: 99%
“…The structures of tryptophan, the dioxo-Mo(VI) complex and various orientations of the complex were first optimized using Hartree-Fock theory and the LanL2DZ basis set. Excited states were modeled using the time-dependent self-consistent-field (TD-SCF) method following computational methodologies described in the literature [33][34][35]. Structures were first optimized in the gas-phase and then in water, where the Polarized Continuum Model (PCM) was used.…”
Section: Computational Chemistrymentioning
confidence: 99%
“…When 1,3-dipolar cycloaddition of pyridinium ylides with electron-deficient olefins or alkynes is followed by oxidative aromatization (spontaneous or chemically induced) a convergent and straightforward access toward functionalized indolizines is arranged. Many excellent examples of this synthetic sequence (cycloaddition/aromatization) have been published (for examples see [75,[77][78][79][80][81][82]) as indolizine is an important skeletal structure present in many natural and synthetic bioactive molecules (for examples see [83][84][85][86][87][88][89][90][91][92][93]) and in material with photochemical properties [94][95][96][97][98][99][100][101][102]. Pivina and co-authors recently reported quantum chemical calculations on the spatial and electronic structure of pyridinium ylides, as well as the modelling of their1,3-dipolar cycloadddition reactions.…”
Section: Pyridinium Ylidesmentioning
confidence: 99%